STUDI KUALITATIF PERSEPSI APOTEKER DAN KADER KESEHATAN DALAM PEMANTAUAN OBAT ANTI TUBERKULOSIS DI PUSKESMAS MLATI II SLEMAN - Nurfadilasari, Ulfa Mustofa; Perwitasari, Dyah Aryani; Supadmi, Woro; Ghozali, MT (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Background: Long-term treatment of tuberculosis can cause side effects that cause concern for patients. The side effects experienced by patients have an impact on treatment compliance and drug withdrawal. Efforts to control drug withdrawal require the role of pharmacists and cadres in monitoring treatment. Objective: to explore the perception of understanding and actions of pharmacists and cadres in monitoring anti-tuberculosis drugs. Method: This study is qualitative study with a case study approach. Participants selection using purposive sampling namely pharmacists, cadres and TB program holders who are involved in monitoring TB treatment. The number of participants was six people. Results: interview transcripts were analyzed thematically using software QSR NVivo 12. We categorized into three themes : drug side effects, medication adherence, and treatment success. Conclusion: pharmacists' understanding and actions in monitoring TB treatment are good. While the cadres' understanding and actions regarding the side effects of drugs are not good enough, the importance of compliance with taking medication and the success of treatment is good